2016
DOI: 10.1080/15475441.2016.1170604
|View full text |Cite
|
Sign up to set email alerts
|

Development of Liaison Representation and its Top-Down Influence on Word Processing in Infants

Abstract: We examined how toddlers process lexical ambiguity where different underlying forms are neutralized at the surface level. In a preferential-looking procedure, French-learning 30-month-olds were familiarized with either liaisonambiguous phrases (i.e., sentences containing a determiner and a non-word, e.g., ces /z/onches, "these onches", "these zonches") (Experiment 1), or nonambiguous (non-liaison) phrases (sentences containing un zonche, "a zonche") (Experiment 2). Infants in both experiments showed a vowel-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 44 publications
1
9
0
Order By: Relevance
“…Children must, therefore, undo liaison by removing the /l/ or /z/ in order to retrieve the verbal item. There is empirical evidence demonstrating that French-learning children can undo liaison by 20 to 24 months of age (Babineau & Shi, 2016). One possibility, then, is that this process in French serves to bring attention to the morphological status of the marker during early acquisition, as evidenced by Frenchlearning children's tendency to undo liaison in the course of comprehending utterances containing novel phrases more often when the liaison consonant was one typically associated with the wordfinal position (e.g., /z/) than with less reliably position-bound consonants (e.g., /t/; cf.…”
Section: Discussionmentioning
confidence: 99%
“…Children must, therefore, undo liaison by removing the /l/ or /z/ in order to retrieve the verbal item. There is empirical evidence demonstrating that French-learning children can undo liaison by 20 to 24 months of age (Babineau & Shi, 2016). One possibility, then, is that this process in French serves to bring attention to the morphological status of the marker during early acquisition, as evidenced by Frenchlearning children's tendency to undo liaison in the course of comprehending utterances containing novel phrases more often when the liaison consonant was one typically associated with the wordfinal position (e.g., /z/) than with less reliably position-bound consonants (e.g., /t/; cf.…”
Section: Discussionmentioning
confidence: 99%
“…Although infants are able to parse consonant-initial words early on, studies on the segmentation of vowel-initial words have consistently shown that these forms are harder to segment (Babineau & Shi, 2014, 2016; Kim & Sundara, 2015; Mattys & Jusczyk, 2001; Nazzi et al, 2005; Seidl & Johnson, 2008). In particular, the ability to extract vowel-initial words from resyllabification contexts takes time to develop, as shown by Mattys and Jusczyk (2001).…”
Section: Variations Ambiguities and The Case Of French Liaisonmentioning
confidence: 99%
“…For instance, a toddler could say les navions instead of les /z/ avions [the planes], possibly due to mis-encoding the form navion from instances such as un /n/ avion [œ̃.navjɔ̃]. It is only after lengthy experience with liaison contexts that French-learning toddlers can gradually learn to counter the onset bias, that is, to ignore the intruding liaison consonant that surfaces at the onset of a vowel-initial word (Babineau & Shi, 2014, 2016). For instance, after hearing a novel vowel-initial word in different contexts yielding variable liaison-consonant onsets (e.g., ces /z/ onches , un /n/ onche , petit /t/ onche , premier /r/ onche ), French-learning 20-month-olds were not able to use the disambiguating subsyllabic distributional cues (i.e., variable liaisons), and they misinterpreted the target as being consonant initial (e.g., zonche ; Babineau & Shi, 2014).…”
Section: Variations Ambiguities and The Case Of French Liaisonmentioning
confidence: 99%
See 2 more Smart Citations